The importance of integrated STEM learning in chemistry lesson: Perspectives from high school and vocational school chemistry teachers - Nur Fitriyana; Antuni Wiyarsi; Heru Pratomo; Marfuatun Marfuatun (OmniaScience, 2024)
Different goals of high schools and vocational schools in Indonesia become the main factor causing the distinction of preparedness of chemistry teachers in using the Science, Technology, Engineering, and Mathematics (STEM) approach in their teaching. Yet the High School Chemistry Teachers (HSCT) and Vocational School Chemistry Teachers (VSCT) need to have positive perceptions about STEM since it offers students meaningful chemistry learning. Through an explorative survey method, this research investigated in-service chemistry teachers' perspectives toward the implementation of STEM in high school and vocational schools of chemistry. A number of 131 in-service chemistry teachers (82 HSCT and 49 VSCT) from Yogyakarta, Indonesia, voluntarily participated in this research through a saturated sampling technique. Perception Scale on STEM (PC-STEM) consisting of 54 closed-ended questions and seven open-ended questions were used as the data collection tools. The data were analysed following content analysis using interpretive coding, descriptive statistics, and the one-way MANOVA test. The findings showed that HSCTs' and VSCTs' perspectives toward STEM fall into the good category. Thus, integrated STEM learning is potential to be used in chemistry lessons at high school and vocational school. However, there were no statistically significant differences in HSCT and VSCT perceptions about the implementation of STEM in chemistry learning. Unfortunately, despite their perception being good, both groups of teachers signified a poor experience in applying STEM in their chemistry lessons. Therefore, teachers' professional development program about STEM is needed for chemistry teachers to implement STEM-based chemistry learning.